Cacao liquor procyanidins prevent postprandial hyperglycaemia by increasing glucagon-like peptide-1 activity and AMP-activated protein kinase in mice. (16th January 2019) - Yamashita, Yoko; Okabe, Masaaki; Natsume, Midori; Ashida, Hitoshi
Abstract: Procyanidins have been reported to possess potential for the prevention of hyperglycaemia. However, there are very few data for procyanidins about the difference the degree of polymerisation (DP) has on anti-hyperglycaemic effects. Moreover, the underlying molecular mechanisms by which procyanidins suppress hyperglycaemia are not yet fully understood. In the present study, we prepared procyanidin fractions with different DP, namely low-DP (DP≤3) and high-DP (DP≥4) fractions, from a cacao liquor procyanidin-rich extract (CLPr). These fractions were administered orally to Institute of Cancer Research (ICR) mice and their anti-hyperglycaemic effects were examined. We found that CLPr and its fractions prevent postprandial hyperglycaemia accompanied by an increase in the plasma glucagon-like peptide-1 (GLP-1) level with or without glucose load. In the absence of glucose load, both fractions increased the plasma insulin level and activated its downstream signalling pathway in skeletal muscle, resulting in promotion of the translocation of GLUT4. Phosphorylation of AMP-activated protein kinase (AMPK) was also involved in the promotion of GLUT4 translocation. High- and low-DP fractions showed a similar activation of insulin and AMPK pathways. In conclusion, cacao liquor procyanidins prevent hyperglycaemia by promoting GLUT4 translocation in skeletal muscle, and both the GLP-1-activated insulin pathway and the AMPK pathway are involved in the underlying molecular mechanism.